Bahnhofsmission als Forschungsgegenstand: diakoniewissenschaftliche Perspektiven - Moos, Thorsten (Evangelische Theologie, 2021)
In this contribution, the railway mission (Bahnhofsmission) is conceived of as an object of research in interdisciplinary diaconic science. To that end, several perspectives are employed: the analysis of the multiple logics/ rationalities of a social organisation; theological hermeneutics of diaconic practice and its religious rationality; and, finally, the question of the location of religion within modern society, for which the railway mission shows to have a paradigmatic meaning.
Gesehen am 25.11.2021
Keywords: Bahnhofsmission